Influencia de la agresividad sobre el rendimiento de equipos de fútbol en España - Garcia-Garcia, P. A.; Martinez, J. A.; González-Gómez, F. J. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
Aggressiveness is a complex concept to define and one which includes actions intended to harm a rival. Such actions can be justified as a means to achieving the goals of the team, or simply a manifestation of explicit violence. The aim of this research was to test whether the belief that aggressive play reaps benefits has empirical support byanalyzing its influence on the variation in the scoring of all matches in the 1st division of the Spanish football league, for the 2007/2008 and 2008/2009 seasons. In order to do so, we distinguished between instrumental and hostile aggression as different levels of aggressiveness. Furthermore, we measured the performance of teams through changes in the scoreboard, that is to say, when a goal is scored. Results derived from the estimation of five different models showed, overall, that aggressiveness has a negative impact on team performance.